Coping with death in Latin American health students in 2024: multinational survey - Real Delor, Raúl E. (2025)
Objective: To describe the frequency of coping with death and to analyze the factors associated with inadequate coping. Materials and methods: An observational and correlational design was applied. The study population was composed with health students in 2024, from several Latin American countries. Sociodemographic variables and coping with Bugen LA's death were measured using a virtual Google Forms™. Results: The sample included 383 respondents, of whom 272 were women (71.1%) with a mean age of 21 ± 7 years and 111 men (28.9%) were 24 ± 8 years. Students from Peru (59.92%) and Paraguay (34.73%) predominated, with the medical career being the most frequent (71.54%). Inadequate coping with death was detected in 191 students (49.87%). Factors significantly associated with poor coping were lower mean age, refusal to be a post-mortem donor, and not having a recent bereavement. Discussion: The poor coping with death of health students affects almost half of them and seems to be related to demographic factors such as the youth of the respondents and social attitudes such as the refusal to be organ donors. Conclusions: Poor coping with death was detected in 49.87%. It is necessary to include competencies during the training of health professionals on how to deal with the death of their patients, since this lack of knowledge can generate stress at work in them.